Burden of dilated perivascular spaces in patients with moyamoya disease and moyamoya syndrome is related to middle cerebral artery stenosis - Han, Guangsong; Fan, Xiaoyuan; Hong, Yuehui; Zhou, Lixin; Zhu, Yicheng; Feng, Feng; Yao, Ming; Ni, Jun (Frontiers in Neurology, 2023)
Background and objective The correlation between intracranial large artery disease and cerebral small vessel disease (CSVD) has become a noteworthy issue. Dilated perivascular spaces (dPVS) are an important marker of CSVD, of which cerebral atrophy has been regarded as one of the pathological mechanisms. DPVS has been found to be associated with vascular stenosis in patients with moyamoya disease (MMD), but the underlying mechanism remains unclear. The purpose of our study was to explore the correlation between the middle cerebral artery (MCA) stenosis and dPVS in the centrum semiovale (CSO-dPVS) in patients with MMD/moyamoya syndrome (MMS) and to determine whether brain atrophy plays a mediating role in this relationship. Methods A total of 177 patients were enrolled in a single-center MMD/MMS cohort. Images of their 354 cerebral hemispheres were divided into three groups according to dPVS burden: mild (dPVS 0–10), moderate (dPVS 11–20), and severe (dPVS > 20). The correlations among cerebral hemisphere volume, MCA stenosis, and CSO-dPVS were analyzed, adjusting for the confounding factors of age, gender, and hypertension. Results After adjustment for age, gender, and hypertension, the degree of MCA stenosis was independently and positively associated with ipsilateral CSO-dPVS burden (standardized coefficient: β = 0.247, P < 0.001). A stratified analysis found that the subgroup with a severe CSO-dPVS burden exhibited a significantly higher risk of severe stenosis of the MCA [p < 0.001, OR = 6.258, 95% CI (2.347, 16.685)]. No significant correlation between CSO-dPVS and ipsilateral hemisphere volume was found (p = 0.055). Conclusion In our MMD/MMS cohort, there was a clear correlation between MCA stenosis and CSO-dPVS burden, which may be a direct effect of large vessel stenosis, without a mediating role of brain atrophy.